FORENSIC LINGUISTICS: FORMS AND PROCESSES - Georgina Heydon (Linguistik Indonesia, 2014)
Following a brief introduction to the notion of forensic science and analysis, this paper will explain the different ways in which linguistics has contributed to police investigations and civil law.  The paper will cover linguistic identification using spoken data and written data, and will discuss the use of discourse analysis as well as the more traditional phonetic and syntactic analysis for forensic examinations.  Other applications that will be discussed include analysis for language of origin in refugee status claims, commercial applications and trademark disputes, and lie detection. Each of these applications will be considered critically and in relation to both the validity of the theories underlying them, and the statistical reliability of the analysis used to attain results.